#TITLE_ALTERNATIVE# - BUCHORI MUSLIM (NIM : 231 01 044);Pembimbing 1 : Dr. Ir. Andi Isra Mahyuddin; Pembimbing 2 :, DEDE
Dynamic analysis of a multibody system could be quickly determined if all elements are rigid. However, due to the needs to increased productivity, higher operating speeds are required. The higher speeds call for lighter members to reduce inertia. This results in structures with flexible members. Hence, the components will be elastically deformed during operation due to relatively high load. The elastic deformation of elements yields the undesirable position. To design the machine that would yield desired accuracy, it is important to understand theses changes in dynamic characteristics. This investigation of the dynamic response is carried out experimentally on a four-bar mechanism with an elastic coupler. The flexibility of the coupler, 250mm x 25mm x 1.6 mm aluminum bar, is introduced through its slenderness. The dynamic response of the coupler is represented by the strain at its midsection, using KGF-02-120-C1-23N30C2 KYOWA strain-gauge. Responses for various crank radii and speed are observed and recorded. Analysis of the responses indicates bifurcation frequency range lower than the coupler bending natural frequency. The results show the bifurcation occurs at frequency equal the 1/3 of its natural frequency.